Pengaruh Lama Perebusan Kedelai Terhadap Karakteristik Kedelai Terfermentasi - Kusuma Putri, Betari Nurrachmah; Suparthana, I Putu; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
This study aims to determine the effect of boiling time of soybean to getting the best fermented soybean characteristics. The design used in this study was a Completely Randomized Design (CRD) with duration of boiling soybeans consisting of 5 levels; 60 minutes, 90 minutes, 120 minutes, 150 minutes, and 180 minutes. This reserach was repeated three times to obtain 15 experimental units. The data obtained were analyzed by analysis of variance and if the treatment had a significant effect, it was continued with the Duncan Multiple Range (DMRT) test. The results showed that 150 minutes of boiling soybean was the best treatment with the criteria of 31,02% mositure content, 1,41% ash content, 18,00% protein content, 15,08% fat content, 34,02% carbohydrate content, light brown color, has a distinctive odor of fermented soybean, has a soft texture, and overall like reception.